New Biomarkers to Predict the Evolution of In Situ Breast Cancers. (26th August 2014) - Bravaccini, S.; Tumedei, M. M.; Scarpi, E.; Zoli, W.; Rengucci, C.; Serra, L.; Curcio, A.; Buggi, F.; Folli, S.; Rocca, A.; Maltoni, R.; Puccetti, M.; et al.
Abstract : Background. Genomic studies have shown that gene expression profiles are similar in in situ (CIS) and invasive breast cancers, suggesting that several biofunctional modifications of the transformation process occur before or during the development of CIS lesion. Methods. We investigated 3 biomarkers in 44 patients with CIS: TG2 (transglutaminase 2), HJURP (Holliday junction recognition protein), and HIF-1α (hypoxia inducible factor-1 alpha). Results. TG2 was more highly expressed than the other two markers and significantly more so in stromal than in tumor cells. HIF-1α evaluation showed a higher expression in both tumor and stromal cells in patients with relapsed G3 tumors, indicating a potential role of this marker in CIS evolution. A greater than sevenfold higher risk of relapse ( P = 0.050 ) was observed in patients highly expressing HJURP in stroma and a tenfold higher recurrence risk ( P = 0.026 ) was seen in those with a higher stromal HIF-1α expression. An important increase in risk accuracy (AUC 0.80) was obtained when HIF-1α and HJURP were evaluated together. Conclusions. Despite the limited number of relapsed patients, we formulated some hypotheses on the factors responsible for malignant evolution and recurrence which are now being tested in a large case series with a longer follow-up.